Environmentally Friendly Compatibilizers from Soybean Oil for Ternary Blends of Poly(lactic acid)-PLA, Poly(ε-caprolactone)-PCL and Poly(3-hydroxybutyrate)-PHB - Garcia-Campo, María Jesús (Materials (Basel), 2017)
Ternary blends of poly(lactic acid) (PLA), poly(3-hydroxybutyrate) (PHB) and poly(ε-caprolactone) (PCL) with a constant weight percentage of 60%, 10% and 30% respectively were compatibilized with soybean oil derivatives epoxidized soybean oil (ESO), maleinized soybean oil (MSO) and acrylated epoxidized soybean oil (AESO). The potential compatibilization effects of the soybean oil-derivatives was characterized in terms of mechanical, thermal and thermomechanical properties. The effects on morphology were studied by field emission scanning electron microscopy (FESEM). All three soybean oil-based compatibilizers led to a noticeable increase in toughness with a remarkable improvement in elongation at break. On the other hand, both the tensile modulus and strength decreased, but in a lower extent to a typical plasticization effect. Although phase separation occurred, all three soybean oil derivatives led somewhat to compatibilization through reaction between terminal hydroxyl groups in all three biopolyesters (PLA, PHB and PCL) and the readily reactive groups in the soybean oil derivatives, that is, epoxy, maleic anhydride and acrylic/epoxy functionalities. In particular, the addition of 5 parts per hundred parts of the blend (phr) of ESO gave the maximum elongation at break while the same amount of MSO and AESO gave the maximum toughness, measured through Charpy’s impact tests. In general, the herein-developed materials widen the potential of ternary PLA formulations by a cost effective blending method with PHB and PCL and compatibilization with vegetable oil-based additives.